DESIGN OF PUBLIC ELECTRIC VEHICLE BATTERY SWAP STATION (PEVBSS) MONITORING SYSTEMS USING THE SERVICE COMPUTING SYSTEM DESIGN FRAMEWORK (CASE STUDY: DIRECTORATE GENERAL OF ELECTRICITY) - Taupik Rahman, A
The escalating global warming, coupled with the use of internal combustion engine vehicles, poses an issue that requires prompt attention. The issuance of Minister of Energy and Mineral Resources Regulation No. 1 of 2023 serves as the basis for developing the Electric Vehicle Battery Swap Station (BSS) Monitoring Information System. This effort aims to create a comprehensive ecosystem for electric vehicles. The primary goal of this research is to design the BSS Monitoring Information System and develop a prototype that can be implemented within the Directorate General of Electricity of the Ministry of Energy and Mineral Resources of the Republic of Indonesia. To support the design and development of the prototype, the researcher has devised a new framework by merging the concepts of Design Science Research (DSR) and Service Computing System Engineering (SCSE), termed as Service Computing System Design (SCSD). The integration aims to bridge the gap between design thinking and engineering thinking, ensuring mutual enrichment of these two methods. The design of the BSS Monitoring Information System using the SCSD framework applies the principles of Service-Oriented Architecture (SOA), making the system design service-centric. The research output includes the SCSD framework and a prototype developed following the stages outlined in the SCSD framework. SCSD is evaluated using a quantitative survey method with the Technology Acceptance Model instrument. The results indicate a positive initial response, with an average acceptance rate of 78.94%, Perceived Usefulness (PU) at 80.32%, and Perceived Ease of Use (PEU) at 77.56%. This suggests that the SCSD approach has the potential to make system design more efficient. Based on SOA-based testing, the design of the SPBKLU Supervision Information System adheres to SOA principles, with a Coupling Factor (CopF) of 0.0018 (Excellent), Cohesion Factor (CohF) of 0.9664 (Excellent), Complexity Factor of 0.0019 (Excellent), and Reusability Factor of 1.3333 (Excellent). Through User Acceptance Testing (UAT) with Focus Group Discussion (FGD) and the results of the User Experience Questionnaire (UEQ), it is concluded that the system is well-received by users. System security testing indicates a low threat level 1, indicating a low level of threat to the system. The prototype results were disseminated with DJK KESDM, ENTREV, and Business Entities, showing the